Analisis Kekuatan Sambungan Pada Belt Conveyor Dengan Metode Mecanical Fastener dan Cold Splicing - Apridiansyah, Apridiansyah; Putri, Fenoria; Hendradinata, Hendradinata (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Belt conveyor is a material transportation tool that uses a belt (belt) as a means of transportation. Belt conveyors were chosen because of their versatile function and ability to work continuously and easy maintenance. The damage factor that often occurs on conveyor belts is tearing and breaking caused by rubbing the belt with the pulley. When the belt breaks or is replaced the connection commonly used is a mechanical fastener and cold splicing connection. In this study, it discusses the strength of the two connections for mechanical fastener connections using flexco and cold splicing connections using 3 different types of adhesives (sunpat eco glue, aibon glue, and dextone glue) drying time of 3 hours. The belt specifications used in this study are EP-100 x 2P x 3.0 x 1.5. to determine the strength of the connection, a tensile test was carried out on the belt connection. From the test results obtained the average value of each connection, mechanical fastener 7.72 MPa, cold splicing glue sunpat eco 8.86 MPa, aibon glue 2.09 MPa, and dextone glue 4.79 MPa. Where the highest tensile strength is obtained by cold splicing joints using sunpat eco glue 8.86 MPa. So from the test results it can be concluded that the cold splicing connection with sunpat eco glue is stronger than other types of conveyor belt connections.